Dampak Penerapan Pola Penggaduhan Terhadap Pengembangan Ternak Sapi Potong Di Kecamatan Padang Jaya Bengkulu Utara - Efendi, Zul; Brata, Bieng; Ishak , Andi; Putranto, Heri Dwi; Barchia, M. Faiz (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Cultivation of beef cattle in Indonesia is mostly carried out by smallholder farms. Therefore, the beef cattle assistance program from the government often involves farmer groups through a livestock raising system. This study aims to determine the impact of implementing various disturbance patterns applied by farmer groups on the development of beef cattle populations. The research was conducted from February to June 2021 in Padang Jaya District, North Bengkulu Regency. Data was collected through interviews with various informants, namely from the Agriculture Office of North Bengkulu Regency, Animal Husbandry Officers from Padang Jaya District, and Management of Farmer Groups. Reports on assistance for the livestock raising program in Padang Jaya District in the 2016-2020 period originating from the Agriculture Service became the basis for searching field information. Eight farmer groups from four recipient villages of the livestock raising program identified the patterns of disturbances and their impact on livestock population development. Secondary data related to this study were collected from BPS reports, Livestock and Animal Health Sector - North Bengkulu District Agriculture Service, and the Padang Jaya District Agricultural Extension Center. The data and information obtained are discussed descriptively. The results showed that there were four patterns of beef cattle raising applied by breeders, namely: (1) one calf deposit, (2) one calf deposit plus Rp. 300,000, (3) deposit of two children, and (4) patterns of rioting with a profit-sharing system. All of these rioting patterns increased the beef cattle population belonging to individual breeders, but only the rioting pattern with the deposit of two calves and a profit-sharing system was able to increase the population of ruminant livestock owned by farmer groups.